Unusual indole alkaloid—epyrrole, —epyrone, and —carbamic acid adducts from Alstonia angustifolia - Kam, Toh Seok; Tan, S.J.; Choo, Y.M.; Thomas, N.F.; Robinson, W.T.; Komiyama, K. (Elsevier, 2012)
Three unusual natural products, viz., alstopirocine, a macroline alkaloid incorporating a substituted pyrrole moiety, pleiomaltinine, an alkaloide—pyrone adduct, and pleiomalicine, an alkaloid—carbamic acid adduct, were isolated from the Malayan Alstonia angustifolia. The alkaloid moiety in alstopirocine was alstomicine while that in pleiomaltinine and pleiomalicine was pleiocarpamine. The structures were determined by spectroscopic methods and in the case of pleiomaltinine, confirmed by X-ray diffraction analysis. Possible biogenetic pathways to these unusual compounds are presented.